The Effect Of Service Quality On Customer Interest In Saving At Islamic Banks With Religiosity As A Moderation Variable - Helma Maraliza (Nomico, 2024)
This study aims to explore the influence of service quality on customer interest in saving in Islamic banks, with religiosity as a moderation variable. The research method used was multiple regression analysis using primary data from 145 respondents of Islamic bank customers in Southeast Sulawesi. The results of the analysis show that the quality of service has a significant positive influence on customer interest in saving at Islamic banks. In addition, the findings also revealed that religiosity plays a role as a moderation variable that strengthens the relationship between service quality and customer interest. The implication of this study is that Islamic banks need to pay attention to and improve the quality of their services, as well as consider religious values in marketing strategies and product development. Thus, the integration between good service quality and awareness of religious aspects can be an effective strategy in increasing customer loyalty and the overall success of Islamic banks.